Digital Marketing Communication - Margherita Corniani (Symphonya, 2006)
Digital marketing communication is directed to profiled targets, which are active in the communication process. Every communication flow can ask for an information answer from the market. This opportunity grants immediate feed-backs and feed-forwards, so that digital communication can be easily and cheaply measured; digital communication flows are diffused at costs that are getting lower and lower, but it asks specialized and deep competences to communication managers. The ease in the flowing process granted by digital technologies is also the main negative aspect of digital communication. It is impossible to control digital flows in all their effect and contacts and this limit opens the door to competitor actions and to “rumors”.